DISCUSSION ABOUT SOME PROBLEMS AND SOLUTIONS AT TEACHING SPEAKING OF ENGLISH AS A FOREIGN LANGUAGE - Yusupova , Sevinch Shuxrat qizi; Ziyodullayeva , Aziza Akmalovna (GOLDEN BRAIN, 2024)
This article is devoted to describe what teaching speaking English is and some problems faced by the teachers and students of English as a Foreign Language (EFL). Speaking is considered one of the urgent skills that need to be acquired by students of EFL. It might become a problem for some EFL teachers to teach students to speak English. This is not a quite easy task for teachers to make their students speak because the language is not spoken in the community. Just as Harmer said (1998:52), to facilitate students with the ‘new’ language, teachers should have students exposed to the language, understand its meaning, understand its form (how it is constructed) and practice it. Therefore, teachers need to change their approach to teaching in order to motivate students to speak. By incorporating activities like role-play, discussions, and games, teachers can create a more engaging speaking class that enhances students' speaking skills.